1981
DOI: 10.1042/bj1970171
|View full text |Cite
|
Sign up to set email alerts
|

The composition and the structure of bacterioferritin of Escherichia coli

Abstract: Bacterioferritin isolated from Escherichia coli is of two kinds: a protein containing a polynuclear iron compound, the bacterioferritin proper and a protein free of the polynuclear iron compound, the apo-bacterioferritin. Bacterioferritin of both kinds is characterized by absorption maxima at 417,530 and 560 nm, contributed by protohaem IX. Single crystals of bacterioferritin of the space group I432 suggest that the molecule is made up of 24 identical subunits related by a cubic point symmetry. The molecular w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(90 citation statements)
references
References 9 publications
4
85
1
Order By: Relevance
“…In region (2) (H < 5 kOe, T> TB) we noted that the magnetization becomes a simple sum of two con tributions as long as the thermal energy exceeds both magnetic energies. Hence the initial 'total' susceptibility XOT in this region becomes a simple sum of two susceptibilities; a superparamagnetic Xp susceptibility and an antiferromagnetic XA susceptibility, (11) In region (4) (H> 20 kOe, T ~ TB)' the super paramagnetic magnetization will saturate, as we have seen in Section 3. netic moment of Fe3+ is 5.92 J.LB' Blaise et al [5,6] has reported a value of ,.., 5.08 JLB for simi lar mammalian ferritin. The difference in these values may be due to the higher density and order of PIC which may increase the number of antiferromagnetic interactions between the atoms, i.e.…”
Section: Magnetic Susceptibilitiesmentioning
confidence: 91%
See 1 more Smart Citation
“…In region (2) (H < 5 kOe, T> TB) we noted that the magnetization becomes a simple sum of two con tributions as long as the thermal energy exceeds both magnetic energies. Hence the initial 'total' susceptibility XOT in this region becomes a simple sum of two susceptibilities; a superparamagnetic Xp susceptibility and an antiferromagnetic XA susceptibility, (11) In region (4) (H> 20 kOe, T ~ TB)' the super paramagnetic magnetization will saturate, as we have seen in Section 3. netic moment of Fe3+ is 5.92 J.LB' Blaise et al [5,6] has reported a value of ,.., 5.08 JLB for simi lar mammalian ferritin. The difference in these values may be due to the higher density and order of PIC which may increase the number of antiferromagnetic interactions between the atoms, i.e.…”
Section: Magnetic Susceptibilitiesmentioning
confidence: 91%
“…Ferritin is an ubiquitous protein, widespread among plants, animals, and in several bacteria, that is designed to store and maintain iron in an available, non-toxic form [11][12][13]. In every case, the molecule consists of a hydrous ferric oxide core sequestered in a roughly spheroidal, 120 A diameter protein shell.…”
Section: Ferritinmentioning
confidence: 99%
“…Six of the seven N-terminal residues of this protein are identical to six of the seven Nterminal residues of Nitrobacter winogradskyi bacterioferritin (BFR) [7] and five are identical to five of the seven N-terminal residues of Escherichia coli BFR [8]. BFR is an iron storage haemoprotein composed of 24 subunits assembled into a spherical protein shell containing approximately 12 haems per 24 subunits [9][10][11] and has been detected in many species [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…[79] First identified from its optical spectrum as cytochrome b 1 in 1934 by Keilin, [80] BFR is a soluble non-toxic iron storage and detoxification protein. [81,82] The expressed protein assembles into a hollow, almost spherical shell-like nanostructure (,8 nm internal diameter) of 24 subunits configured as a dodecameric structure (Fig. 3a).…”
Section: Modified Bacterioferritin As a Photoactive Reaction Centrementioning
confidence: 99%